2017
DOI: 10.1021/acs.joc.7b01115
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Pestalotioprolide G and Putative Structure of Pestalotioprolide H

Abstract: A concise and convergent route for the stereoselective total synthesis of cytotoxic macrolides pestalotioprolides G and H has been developed for the first time. Intramolecular Heck coupling has been chosen to cyclize the 14-membered macrocycle. This synthetic study strongly suggests that the proposed structure of pestalotioprolide H may need to be corrected as the spectroscopic data on the synthesized molecule deviate from the values reported for the isolated natural product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…also led to structural revision of the NP to 837, the diatereoisomer of the originally proposed structure. 321 The 14-membered ring macrolides, pestalotioprolide C 322 and pestalotioprolide G 323 have been synthesised and mismatch of the spectroscopic data of the synthesised proposed structure of pestalotioprolide H and that of the isolated metabolite indicated that structural revision of the NP is required. 323 Fused tetrahydrofuran lactone 2106 A (unidentied endophytic fungus, Avicennia marina) has been synthesised via an approach utilising radical addition to activated olens.…”
Section: Fungi From Mangrovesmentioning
confidence: 99%
See 1 more Smart Citation
“…also led to structural revision of the NP to 837, the diatereoisomer of the originally proposed structure. 321 The 14-membered ring macrolides, pestalotioprolide C 322 and pestalotioprolide G 323 have been synthesised and mismatch of the spectroscopic data of the synthesised proposed structure of pestalotioprolide H and that of the isolated metabolite indicated that structural revision of the NP is required. 323 Fused tetrahydrofuran lactone 2106 A (unidentied endophytic fungus, Avicennia marina) has been synthesised via an approach utilising radical addition to activated olens.…”
Section: Fungi From Mangrovesmentioning
confidence: 99%
“…321 The 14-membered ring macrolides, pestalotioprolide C 322 and pestalotioprolide G 323 have been synthesised and mismatch of the spectroscopic data of the synthesised proposed structure of pestalotioprolide H and that of the isolated metabolite indicated that structural revision of the NP is required. 323 Fused tetrahydrofuran lactone 2106 A (unidentied endophytic fungus, Avicennia marina) has been synthesised via an approach utilising radical addition to activated olens. 324 A study of the effect of monochromatic red, blue and green light on polyketide production in an endophytic Halorosellinia sp.…”
Section: Fungi From Mangrovesmentioning
confidence: 99%
“… [87] Selecting the Heck reaction over the Sonogashira coupling was driven by difficulties found during a C13‐C14 alkyne selective reduction. The Heck reaction was also utilised by Goswami in the total synthesis of the 14‐membered macrocycle pestalotioprolide G, where it concomitantly performed the macrocyclisation step and installed the E,Z ‐diene unit [88] …”
Section: Stereoselective Methodsmentioning
confidence: 99%
“…The Heck reaction was also utilised by Goswami in the total synthesis of the 14-membered macrocycle pestalotioprolide G, where it concomitantly performed the macrocyclisation step and installed the E,Z-diene unit. [88]…”
Section: Heck Reactionsmentioning
confidence: 99%
“…Compound 61 was then transmuted to another natural product hapalonamide H (62) in one step. In 2018, Dethe et al [25b] used intramolecular Heck reaction as an important step to achieve the total synthesis of (+)-hapalindole H (61) and its C12-epimer (65).…”
Section: Ergot Alkaloidsmentioning
confidence: 99%